The Role of Sustainability Accounting: Environmental, Social and Economic Accountability - Suhendar; Inova Fitri Siregar; Ridwansyah (PT Inovasi Pratama Internasional, 2023)
The aim of this study to get empirical evidence about how the role of sustainability accounting is seen from the accountant's point of view on its social, environmental and economic accountability, then how is the readiness of academics, accountants, stakeholders in achieving the implementation of design guidelines for measuring, recording, reporting and presenting sustainability accounting. With proper design, measurement and application, it is hoped that the implementation of sustainable accounting and sustainable reporting will have a significant positive impact on the development of accounting both as a science and as an engineering technology. The second is the accounting profession or accounting graduates in job development or professions. Third, increasing the strategic role of accounting information in business, economic, political, social, legal. The method in this study was to use quantitative and qualitative methods with purposive sampling and multiple regression methods, where the determination of the sample used several criteria, namely accounting lecturers and accountants in Riau Province, then there were 142 accounting lecturers and accountants who were included in this category. The results of the study show the influence of the role of sustainability accounting on accountability in environmental aspects and reporting of sustainability accounting information while in the economic and social aspects there is no influence on the role of sustainability accounting.